Percutaneous intervention of severe native coarctation of the aorta presenting in pregnancy: a case report. Issue 3 (17th February 2023) - Nashat, Heba; Patel, Roshni; Johnson, Mark R; Rafiq, Isma
Abstract: Background: Coarctation of the aorta (CoA) is one of the more common congenital heart defects affecting up to 5% of patients with congenital heart disease. Pregnant patients with unrepaired or severe re-coarctation are considered to be modified World Health Organisation (mWHO) IV, have the highest risk of maternal mortality and morbidity. The management of unrepaired CoA during pregnancy is influenced by a variety of factors which include the extent of the coarctation and coarctation characteristics, but due to paucity of data, it largely relies on expert opinion. Case summary: A 27 year old multi-gravid woman underwent successful percutaneous stent implantation for severe native CoA due to maternal resistant hypertension and foetal cardiac compromise on echocardiography. After intervention, the remainder of her pregnancy was uneventful with improved arterial hypertension control. The foetal cardiac structures, namely left ventricular size, improved after intervention. This case demonstrates the importance of CoA intervention during pregnancy to optimise both maternal and foetal outcome. Conclusion: Coarctation of the aorta should be considered in pregnant women with poorly controlled hypertension. This case also highlights that, despite associated risks, percutaneous intervention can lead to improved maternal haemodynamics and fetal growth.